2019
DOI: 10.1021/acs.orglett.9b02683
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Scale Synthesis and Supramolecular Complex of Precursors of Clar’s Hydrocarbon Triangulene

Abstract: We present to date the most efficient gram-scale synthesis of triangulene-4,8-dione and 12-hydroxytriangulene-4,8-dione, the precursors of Clar’s hydrocarbon, in overall yields >50%. The direct dihydroprecursors of triangulene, obtained upon reduction of triangulene-4,8-dione, were stabilized in a supramolecular complex with a tetracationic cyclophane ExBox4+ and characterized by single-crystal X-ray crystallography. This result represents the first step in an endeavor to stabilize the fragile core of triangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The first molecular‐scale preparations of higher homologues [4]‐ and [5]triangulene have very recently been reported as further milestones in this rapidly evolving field. Di‐ and tetrahydro[3]triangulenes are now more available through this work and a parallel study reported recently by Juríček and co‐workers . Our preliminary efforts to generate [3]triangulene in the solution phase provide evidence for rapid oligomerization, as might be expected for this highly reactive substance.…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…The first molecular‐scale preparations of higher homologues [4]‐ and [5]triangulene have very recently been reported as further milestones in this rapidly evolving field. Di‐ and tetrahydro[3]triangulenes are now more available through this work and a parallel study reported recently by Juríček and co‐workers . Our preliminary efforts to generate [3]triangulene in the solution phase provide evidence for rapid oligomerization, as might be expected for this highly reactive substance.…”
Section: Figuresupporting
confidence: 68%
“…Di-and tetrahydro [3]triangulenes are now more available through this work and ap arallel study reported recently by Juríček and co-workers. [34] Our preliminary efforts to generate [3]triangulene in the solution phase provide evidence for rapid oligomerization, as might be expected for this highly reactive substance.W ebelieve it should be possible to tame the solution phase reactivity of 2 through appropriate chemical traps.…”
Section: Theproducts Inmentioning
confidence: 83%
See 1 more Smart Citation
“…[12] In its purely organic covalent variant, Cid and co-workers have demonstrated the feasibility of realizing chiral molecular cages with outstanding chiroptical properties from the combination of shape-persistent enantiopure DEAs and simple aromatic motifs for the detection of small achiral molecules (Figure 1, cages 1 and 2). [13][14][15] On this firm basis, we advocate the use of bridged triarylamines, known as N-heterotriangulenes (N-HTAs), in the role of chromophoric aromatic lids, in order to achieve redox-active nanosized cavities [16][17][18][19][20] for larger chiral guests, aiming at setting foot on the realm of enantioselective discrimination. [21][22][23] Precedents of sensing examples involving triarylamines range from the detection of metallic cations, [24] to toxic anions [25] or anions present in chemical weapons, [26] nitroaromatic explosives, [27] biological metabolites, [28] toxic gases, [29,30] and pH determination.…”
mentioning
confidence: 99%
“…Further development in the evolving triangulene field requires efficient syntheses. Earlier synthetic routes to the all‐carbon ring system of 2 are relatively lengthy; improvements in the Clar route to triangulene precursors have been reported as this work was under review . We report here a very short and efficient synthesis of the [3]triangulene ring system by cascade cyclization that provides multiple precursors to 2 and potential derivatives.…”
Section: Figurementioning
confidence: 99%